(untitled) (Cadernos de Sociomuseologia, 2022)
This article was born as a result of listening to several communications within the scope of Paulo Freire’s Centenary together with readings that were being made for my PhD thesis, born of a happy encounter between both activities. It is not possible to see only an Educator, a Philosopher or a Sociologist, nor to see Paulo Freire as a Social Museologist. Paulo Freire assumes himself as a complete man when he represents the true role of Philosophy, as the mother of the sciences and as the love of wisdom. It is not possible to see in Paulo Freire only the human being, limited to a space and time, because there are outside these universes of meaning. It is not possible to see Paulo Freire as anything less than his will, a will that continued to exist in the two prisons he faced, his prison, the result of a military system that works out of fear and control, and his Death, where his will goes out in the last breath. Will be? I choose to see in Paulo Freire the sum of all sciences, whether exact or relative (i.e. social sciences). I choose to see Paulo Freire outside any categorical universe belonging to the human condition. I choose to see Paulo Freire as a desiring machine that faces the designs of mortality. That in this publication, we are like Fates, weaving once again the life, work and legacy of this Master. Keywords: Sociomuseology; Education; Freedom; knowledge; Dialogue